2022
DOI: 10.3389/fmolb.2022.799703
|View full text |Cite
|
Sign up to set email alerts
|

Host Cell Glycocalyx Remodeling Reveals SARS-CoV-2 Spike Protein Glycomic Binding Sites

Abstract: Glycans on the host cell membrane and viral proteins play critical roles in pathogenesis. Highly glycosylated epithelial cells represent the primary boundary separating embedded host tissues from pathogens within the respiratory and intestinal tracts. SARS-CoV-2, the causative agent for the COVID-19 pandemic, reaches into the respiratory tract. We found purified human milk oligosaccharides (HMOs) inhibited the viral binding on cells. Spike (S) protein receptor binding domain (RBD) binding to host cells were pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 82 publications
0
12
1
Order By: Relevance
“…Interestingly, some studies have indicated that altering the host glycosylation can effectively inhibit viral binding to the host. Particularly, human milk oligosaccharides that are heavily decorated with α−2,6‐sialyl‐lactose are capable of preventing SARS‐CoV‐2 infection (Moore et al, 2021 ; Sheng et al, 2022 ). In‐depth characterization of the viral glycoproteome is therefore vital to understand the roles of SARS‐CoV‐2 in host‐pathogen mechanisms.…”
Section: Glycoproteomics‐based Ms Of Sars‐cov‐2 Viral Proteinsmentioning
confidence: 99%
“…Interestingly, some studies have indicated that altering the host glycosylation can effectively inhibit viral binding to the host. Particularly, human milk oligosaccharides that are heavily decorated with α−2,6‐sialyl‐lactose are capable of preventing SARS‐CoV‐2 infection (Moore et al, 2021 ; Sheng et al, 2022 ). In‐depth characterization of the viral glycoproteome is therefore vital to understand the roles of SARS‐CoV‐2 in host‐pathogen mechanisms.…”
Section: Glycoproteomics‐based Ms Of Sars‐cov‐2 Viral Proteinsmentioning
confidence: 99%
“…According to the pseudotyped lentivirus and authentic virus infection data, acidic host N -glycans may serve as viral attachment factors. Contrary to previously reported findings, oligomannose N -glycans are found not to be RBD ligands . Finally, the screening data provide irrefutable evidence that SARS-CoV-2 RBD recognizes sialoglycans.…”
Section: Resultsmentioning
confidence: 99%
“…63 Based on this finding and the observation that RBD binding to host cells is reduced upon incubation with oligomannose glycans, it was concluded that cell surface oligomannose glycans increase adherence of RBD. 63 However, in the current study, as well as previous screening studies, oligomannose N-glycans are not detected as RBD ligands. 57 To gain further insight into the host cell Nglycans on SARS-CoV-2 infection, we performed pseudotyped lentivirus infection of ACE2-expressing HEK293T cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Targeting glycoproteins is an underexploited strategy for the development of cancer therapeutics. Carbohydrate-active enzymes such as glycosidases and glycosyltransferases are attractive drug targets due to their involvement in the biosynthesis of glycan structures. , Relatively few studies have investigated potential small molecule inhibitors with drug-like properties against these enzymes. These include plant alkaloids that inhibit glycosidases by inducing inhibition of trimming reactions after the attachment of Glc 3 Man 9 GlcNAc 2 oligosaccharide. An example of a plant alkaloid is swainsonine from an Astralagus species known as locoweeds.…”
Section: Introductionmentioning
confidence: 99%